2010
DOI: 10.1007/s10549-010-0820-4
|View full text |Cite
|
Sign up to set email alerts
|

Loss of ICAM-1 signaling induces psoriasin (S100A7) and MUC1 in mammary epithelial cells

Abstract: Psoriasin (S100A7), a member of the S100 gene family, is highly expressed in high-grade comedo ductal carcinoma in situ (DCIS), with a higher risk of local recurrence. Psoriasin is therefore a potential biomarker for DCIS with a poor prognosis. High-grade DCIS is characterized by a high proliferation rate and crowded cells consequently lose contact with the extracellular matrix. The aim of the present work was therefore to elucidate the involvement of adhesion signals in the regulation of psoriasin. Protein ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…The finding that psoriasin induces the expression of both VEGF and IL-8 in dermal endothelial cells, in parallel with the findings of induced cell proliferation, support the notion of VEGF and IL-8 as mitogenic factors for endothelial cells and illustrates the importance of psoriasin. Previous results describe a negative correlation between THBS-1 and psoriasin expression in normal and DCIS specimens [146]. In agreement with those findings, we detected a significant increase in THBS-1 expression in H 2 O 2 -treated keratinocytes where the psoriasin expression was down-regulated.…”
Section: Paper IIsupporting
confidence: 92%
See 1 more Smart Citation
“…The finding that psoriasin induces the expression of both VEGF and IL-8 in dermal endothelial cells, in parallel with the findings of induced cell proliferation, support the notion of VEGF and IL-8 as mitogenic factors for endothelial cells and illustrates the importance of psoriasin. Previous results describe a negative correlation between THBS-1 and psoriasin expression in normal and DCIS specimens [146]. In agreement with those findings, we detected a significant increase in THBS-1 expression in H 2 O 2 -treated keratinocytes where the psoriasin expression was down-regulated.…”
Section: Paper IIsupporting
confidence: 92%
“…In normal epithelial cells the MUC1 expression is weak to moderate. In DCIS, the expression is strong and corresponds to the expression of psoriasin [146]. CD24 has been shown to be a marker of tumor aggressiveness and the expression of CD24 promotes breast cancer development [168][169][170].…”
Section: Paper IIImentioning
confidence: 99%
“…Recently, we demonstrated that psoriasin correlates negatively with Intercellular adhesion molecule 1 (ICAM-1) and positively with Mucin1 (MUC1) [12]. Similar to VEGF we have previously demonstrated that psoriasin is induced by ROS [13].…”
Section: Introductionmentioning
confidence: 71%
“…In pancreatic cancer, the expression of S100A4 and S100P was associated with drug resistence, differentiation, metastasis and clinical outcome and S100A11 and S100P, and possibly also S100A2 and S100A6 were related to the unfavorable outcome of the patients after surgical resection 61 . S100A7/psoriasin was highly expressed in high-grade ductal breast carcinoma in situ 62 , high-grade comedo ductal carcinoma in situ with higher risk of local recurrence 63 and in invasive estrogen receptor negative breast cancer 64 . Its expression was related to ductal hyperplasia, recruitment of tumor-associated macrophages, tumor growth, angiogenesis and metastasis.…”
Section: S100 Proteins and Cancermentioning
confidence: 99%